Birth Assistance and Delivery Methods in the Practice of Early Breastfeeding Initiation at Kasih Fatimah Maternity and Children's Hospital - Rahmini Shabariah; Wira Aditya Potabuga; Farsida Farsida; Rayhana Rayhana; Tri Ariguntar Wikanningtyas (GLOBAL HEALTH SCIENCE GROUP, 2024)
Worldwide, approximately three million infants die every year in their first month of life, and 22.3% of neonatal deaths can be prevented with Early Initiation of Breastfeeding (EIBF). Immediate breastfeeding initiation after birth is an integral part of safe delivery procedures and is widely recognized as a beneficial practice. Delayed breastfeeding initiation has been found to increase the risk of mortality among newborns. Objective: The aim of this study is to determine the relationship between birth attendants and delivery methods with EIBF at Kasih Fatimah Maternity and Children’s Hospital. Method: A descriptive-analytic approach using a cross-sectional design was employed, involving 80 samples selected through consecutive sampling. Results: The study revealed that 77 respondents (96.3%) initiated breastfeeding within <1 hour, with 62.5% of patients assisted by midwives, and 62.5% giving birth via vaginal delivery. No significant relationship was found between birth attendants and delivery methods with EIBF (p>0.05). Conclusions: Although these results demonstrate a high level of EIBF practice and no significant association with EIBF, there is potential for improvement in the implementation of EIBF procedures in the hospital.